When an Industry Peer Is Accused of Financial Misconduct: Stigma versus Competition Effects on Non-accused Firms - Naumovska, Ivana; Lavie, Dovev (Administrative Science Quarterly, 2021)
Research on misconduct suggests that accusations against industry peers generate negative consequences for non-accused firms (a “stigma effect”). Yet, building on research on competitive dynamics, we infer that such accusations can benefit non-accused firms that compete with these peers (a “competition effect”). To reconcile these opposing perspectives, we posit that the negative stigma effect will increase with greater product market overlap between the non-accused firm and its accused peer, up to a point, beyond which the positive competition effect will counterbalance it. We further conjecture that the competition effect will be relatively more pronounced when the market classification used by investors for assessing the market overlap is more fine-grained. Accordingly, we suggest that more sophisticated investors, who rely on more fine-grained market classifications, increase their shareholdings in non-accused firms to a greater extent than less sophisticated investors as the market overlap between the non-accused firm and the accused peer increases. Using elaborate data on products and investments, we analyze investors’ shareholdings and stock market returns of non-accused firms in the U.S. software industry following accusations of financial misconduct by their industry peers, and we find support for our predictions. Our study elucidates the interplay between stigma and competition following misconduct by industry peers.